Peripartum dilated cardiomyopathy complicated with renal infarction - Rojas-Lazaro, Janet (2019)
Peripartum cardiomyopathy is a form of dilated cardiomyopathy that affects women of childbearing age, causing high morbidity and mortality. We present the case of a young primiparous patient with symptoms of heart failure who also suddenly presented high intensivity low back pain associated with nausea and vomiting. Laboratory test reports high levels of serum lactic dehydrogenase, and urinary tract tomography was ordered. The diagnosis of heart failure with severe systolic dysfunction and renal infarction were severe systolic dysfunction was demonstrated. Treatment with conventional measures for heart failure was performed, parenteral and oral anticoagulation was used.The evolution of the clinical picture was favorable, with partial recovery of its functionality. This case is presented due to the atypical complication of an infrequent or under-diagnosed pathology.